TAX PLANNING ATAS PAJAK PENGHASILAN BADAN PADA SEMUA PERSEKUTUAN KOMANDITER (CV) DI KOTA LUBUKLINGGAU DAN KOTA BENGKULU - Dheo Rimbano; Mirra Sri Wahyuni (Creative Research Management Journal, 2018)
Corporate income tax that must be paid. Neither, awareness of paying is poor, Islam is more familiar with the term â€œZakatâ€ than tax (Awareness in paying zakat is â€˜very highâ€™ for Muslims). We know, raising awareness begins with the planning process, so the constraints in every plan to pay taxes need to be known. Possible taxpayers already know of its obligations, but the meaning is like a "double-edged knife", the positive trend in paying taxes is still to be studied, whether based on the tax amnesty and or if the tax planning starts, the negative side of tax amnesty is the fact that our taxpayers are "stubborn" In the discipline of paying taxes. With the existence of tax planning, the taxpayer can save tax that actually exceeds its obligations, and on the other hand help taxpayers in making decisions relating to investment plans in the future. The research focus is on the scope of Tax Planning with Law No. 36 of 2008 concerning Income Tax and Tax Regulations others in all the Command Companies in Lubuklinggau City and Bengkulu City. Using qualitative analysis, to analyze tax planning for corporate income tax. then consider the actions that should be taken in streamlining the 2015 owed Corporate Income Tax under Law No. 36 of 2008 article 9 paragraph (1) and Law No. 36 of 2006 article 9 paragraph (1) letter e, activities can be carried out as follows: (1) Provision of health benefits for employees; (2) Providing HR development and education for employees; (3) Provision of bonuses for employee performance; (4) Provision of vehicles for transportation; and (5) giving uniforms to employees. The results of the study show that (1) the Tax Planning of the PPH the Agency in accordance with the Tax Regulations the majority of the CVs are not implemented and (2) In the financial management of CVs both in Lubuklinggau City and Bengkulu City have not been able to make efficient PPH payments.